2008
DOI: 10.1002/jssc.200700443
|View full text |Cite
|
Sign up to set email alerts
|

High throughput screening and antioxidant assay of dibenzo[a,c]cyclooctadiene lignans in modified‐ultrasonic and supercritical fluid extracts of Schisandra chinensis Baill by liquid chromatography–mass spectrometry and a free radical‐scavenging method

Abstract: Dibenzo[a,c]cyclooctadiene lignans of Schisandra chinensis Baill are well known because of their hepatoprotective activity, antioxidant activity, and anticancer effect. For the isolation of the dibenzo[a,c]cyclooctadiene lignans of Schisandra chinensis Baill two extraction methods were used: modified-ultrasonic extraction and supercritical fluid extraction. A specific and fast analytical method for structure identification is established for quality control because structure elucidation could be accomplished b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 35 publications
1
17
0
Order By: Relevance
“…Wang et al (2014) reported ORAC values of 1.01 and 1.3 mmol TE/L of normal and lignan enriched juices of S. chinensis, whereas Kim et al (2009) found an 11.9% inhibition in ABTS assay for a fruits methanolic extract. Further, Wang et al (2008) described a 30.1% DPPH inhibition by a S. chinensis fruits extract. Furthermore, these authors link the antioxidant activity of the fruits with their content in gomisin J, gomisin F, tigloylgomisin P, gomisin M1/M2/L1/L2.…”
Section: Photometric Trolox Equivalence Antioxidant Capacity -(Offlinmentioning
confidence: 97%
See 2 more Smart Citations
“…Wang et al (2014) reported ORAC values of 1.01 and 1.3 mmol TE/L of normal and lignan enriched juices of S. chinensis, whereas Kim et al (2009) found an 11.9% inhibition in ABTS assay for a fruits methanolic extract. Further, Wang et al (2008) described a 30.1% DPPH inhibition by a S. chinensis fruits extract. Furthermore, these authors link the antioxidant activity of the fruits with their content in gomisin J, gomisin F, tigloylgomisin P, gomisin M1/M2/L1/L2.…”
Section: Photometric Trolox Equivalence Antioxidant Capacity -(Offlinmentioning
confidence: 97%
“…While some authors propose that lignans are good antioxidants and suggest the enrichment of several food products with these compounds in order to enhance their antioxidant properties (Kim, Lee, Do, & Bang, 2015;Kim & Choi, 2014), others state that their radicalscavenging properties are moderate and only effective at high concentrations (Šmejkal et al, 2010). Furthermore, antioxidant capacities of featured constituents and corresponding herbal preparations were mostly determined by (offline) bioassays such as the (traditional) DPPH, FRAP, or TEAC assays (Liu et al, 2009;Mocan et al, 2014;Wang et al, 2008). However, these methods cannot directly determine and identify the active components in herbal mixtures requiring further tedious separation and purification procedures, which are time consuming, produce a lot of waste, and do not always lead to expected results.…”
Section: 2mentioning
confidence: 99%
See 1 more Smart Citation
“…Wuweizi has high content of lignans, which mainly exist in seeds (4.1~19.2% of whole fruit) [1]. The lignans have been considered as the primary constituents for Wuweizi’s antioxidant, hepatoprotective, immuo-modulating, anti-inflammatory and anticancer effects [6]. Compared to the intensive studies on lignans, polyphenols in Wuweizi pulp, especially anthocyanins have not received much attention.…”
Section: Introductionmentioning
confidence: 99%
“…[1415] Pharmacological studies have shown that some of the metabolites exhibit various properties, such as antihepatotoxic, antimicrobial, hypoglycaemic, antiallergic, anti-inflammatory, antioxidant, and anti-cancer effects. [1617181920] Although schizandrin, the main constituent of SF, showed inhibitory activity on passive cutaneous anaphylaxis induced by the IgE-antigen complex, well-controlled clinical trials, or translational research on SF for asthma treatment are rare. [11]…”
Section: Introductionmentioning
confidence: 99%